2017
DOI: 10.3389/fncir.2017.00041
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Substrates of Rodent Social Behavior: The Medial Prefrontal Cortex and Its Projection Patterns

Abstract: Social behavior encompasses a number of distinctive and complex constructs that form the core elements of human imitative culture, mainly represented as either affiliative or antagonistic interactions with conspecifics. Traditionally considered in the realm of psychology, social behavior research has benefited from recent advancements in neuroscience that have accelerated identification of the neural systems, circuits, causative genes and molecular mechanisms that underlie distinct social cognitive traits. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
135
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(143 citation statements)
references
References 237 publications
(320 reference statements)
7
135
0
1
Order By: Relevance
“…Our results contradict previous studies that report no IEG induction in the CA2 region of the hippocampus upon social stimuli Tanimizu et al, 2017), while supports findings from Kim et al that report CA2 activation upon social interaction (Kim et al, 2015). The hippocampus is critically integrated into the rodent circuitry involved in social behaviours (Kim et al, 2015;Ko, 2017;Kogan et al, 2000;Raam et al, 2017;, but specifically, the CA2 subfield is important for the formation of social memory Hitti and Siegelbaum, 2014;Leroy et al, 2017;Lin et al, 2017;Smith et al, 2016;Stevenson and Caldwell, 2014). Therefore, it is no surprise that we observe neuronal activation in the CA2 region upon social stimuli, a prerequisite to social memory formation (Felix-Ortiz and Tye, 2014;Hitti and Siegelbaum, 2014).…”
Section: Discussionsupporting
confidence: 65%
“…Our results contradict previous studies that report no IEG induction in the CA2 region of the hippocampus upon social stimuli Tanimizu et al, 2017), while supports findings from Kim et al that report CA2 activation upon social interaction (Kim et al, 2015). The hippocampus is critically integrated into the rodent circuitry involved in social behaviours (Kim et al, 2015;Ko, 2017;Kogan et al, 2000;Raam et al, 2017;, but specifically, the CA2 subfield is important for the formation of social memory Hitti and Siegelbaum, 2014;Leroy et al, 2017;Lin et al, 2017;Smith et al, 2016;Stevenson and Caldwell, 2014). Therefore, it is no surprise that we observe neuronal activation in the CA2 region upon social stimuli, a prerequisite to social memory formation (Felix-Ortiz and Tye, 2014;Hitti and Siegelbaum, 2014).…”
Section: Discussionsupporting
confidence: 65%
“…Here, we demonstrate that in rodents, prenatal stress leads to alterations in microbiota in adult males, as well as decrease in social behavior, and alterations in cortical neurobiology including reduction in serotonin turnover, elevated markers of neuroinflammation, alterations in CRH axis, and concomitant reduction in OXTR. Social behavior is mediated by multiple neural circuits and brain regions [23]; cortical dysfunction has previously been tied with social behavior in both humans and rodents [24,25]. To our knowledge this is the first time in males that the gut microbiota has been considered in the link between PNS, social behavior, and concomitant alterations in cortical neurobiology.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced anxiety‐like responses observed here in CD38 −/− mice could also contribute to alteration of social behavior. This view is largely supported by the strong comorbidity of anxiety disorders with social cognitive disorders and by the involvement of an integrated brain circuit including amygdala, hypothalamus, and PFC in the control of innate social behaviors such as aggression and parenting responses [(79) for a review]. Previous studies in CD38 −/− mice reported variable effects of CD38 loss of function on anxiety and parenting behaviors (29, 80).…”
Section: Cussionmentioning
confidence: 99%